Association diastolic function by echo and infarct size by magnetic resonance imaging after STEMI. (3rd May 2016) - Søholm, Helle; Lønborg, Jacob; Andersen, Mads J.; Vejlstrup, Niels; Engstrøm, Thomas; Hassager, Christian; Møller, Jacob Eifer
Abstract: Objectives . Left ventricular (LV) diastolic dysfunction is a predictor of increased morbidity and mortality; however, little is known about diastolic function and the degree of myocardial damage after myocardial infarction (MI). The aim was to assess the association between diastolic dysfunction by echocardiography and myocardial salvage assessed with cardiac magnetic resonance (CMR) imaging in patients with ST-segment elevation MI (STEMI). Design . In a prospective study, echocardiography and CMR were performed in STEMI patients in the early post-MI phase assessing diastolic dysfunction according to E / A and E / e 'average and area at risk, and after three months with measurement of final infarct size and salvage index. Linear regression analyses were performed testing the association of diastolic dysfunction with area at risk, final infarct size and salvage index. Results . A total of 193 patients (61 ± 11 years) were included. Median system delay (first medical contact to primary PCI) was 185 min, 123 patients (63%) had TIMI 0/1 flow before intervention and 85 (46%) sustained an anterior MI. In 74 patients (38%), diastolic function was normal. The presence of diastolic dysfunction was associated with larger area at risk of median 6.6% (p < 0.001), larger final infarct size of 4.5% (p < 0.001), and lower salvage index of −5.9% (p = 0.02) compared with patients with normal diastolic function. Conclusion. Diastolic dysfunction in the early phase after STEMI is associated with more extensive myocardial damage and significantly poorer myocardial salvage after three months, and the presence of diastolic dysfunction acutely after STEMI may therefore be used as a marker of worse myocardial outcome.